Correlation between patellar tendon morphology and running critical power across different running surfaces - Jaén-Carrillo, D.; Lawley, J. S.; Rubio-Peirotén, A.; Cartón-Llorente, A. (International Journal of Sports Science & Coaching, 2025)
Trail running is an exponentially growing sport whose particular characteristics mean that athletes must adapt their running biomechanics, thus generating different physiological demands. A useful key to monitor the performance of this athletes is critical power (CP). This study aims to analyze the effects of two distinct running surfaces (i.e., athletic track and groomed trail) on CP, and the correlation between patellar tendon morphology and running performance metrics on these surfaces. 23 highly trained trail runners completed two maximum effort races (9' and 3') in two different surface sessions (track and trail) where CP and spatiotemporal parameters were recorded with the Stryd power meter. A patellar tendon ultrasound assessment was performed to assess the relation of the connective tissue morphology with running surfaces. Significant differences in CP and all the spatiotemporal variables between track and trail, except for mean CP during the 9-min test. Additionally, moderate to large correlations (0.39 = r = 0.56) were found between patellar tendon CSA and all the running variables for the 9- and 3-min running test and CP. Patellar tendon CSA positively correlates with performance in both track and trail conditions, but its impact is more pronounced in trail running where biomechanical adjustments are necessary therefore part of the training should be oriented in this direction.